Economic effects of natural disasters - Tatyana Deryugina (IZA World of Labor, 2022)
Extreme weather events are increasing in frequency and intensity, threatening lives and livelihoods around the world. Understanding the short- and long-term effects of such events is necessary for crafting optimal policy. The short-term economic impacts of natural disasters can be severe, suggesting that policies that better insure against consumption losses during this time would be beneficial. Longer-term economic impacts are more complex and depend on the characteristics of the affected population and the affected area, changes in migration patterns, and public policy.
Keywords: Q54; O15; J01; 330; natural disasters; disaster aid; migration; labor market outcomes; health effects